Origin and role of gap states in organic semiconductor studied by UPS: as the nature of organic molecular crystals. (27th September 2017) - Yang, Jin-Peng; Bussolotti, Fabio; Kera, Satoshi; Ueno, Nobuo
Abstract: This article reviews experimental studies on 'bridging electronic structure and charge transport property of organic semiconductors' performed using ultraviolet photoelectron spectroscopy (UPS) and related methods mainly in Chiba University, Japan, in particular on the investigation of the origin and the role of electronic states existing in the highest occupied molecular orbital band–lowest unoccupied molecular orbital band (HOMO–LUMO) gap. We summarize experimental observations including direct measurements of 'invisible' gap states with ultrahigh sensitivity UPS, which demonstrate that there exist intrinsic gap states in organic semiconductors. We firstly describe the nature of organic molecular solids to understand features of organic semiconductors because such intrinsic gap states are a result of the interplay of these features, which give the principal difference between the organic semiconductor and inorganic counterpart. We then discuss (i) the origin and role of the band gap states in relation to intermolecular interaction/band dispersion and electron–phonon coupling, (ii) the Fermi level pinning issue in organic semiconductors, and (iii) the method of computing the Fermi level position within the HOMO–LUMO gap for experimental groups. The gap states of organic semiconductors appear easily when a weak perturbation is applied to the organic system, namely by contact with other material, by injecting a charge, by elevating temperature, and by exposure to 1 atm gas. What we finally found is that tailing states of HOMO and LUMO always exist, and their energy distributions must not be symmetric; they thus produce a larger Fermi level shift from the mid gap position than previously thought. Furthermore, as shown by computational work, Fermi level pinning, which is a well-known phenomena in semiconductor devices field, occurs in weakly interacting organic/conductor systems without any gap states if the system temperature is not zero ( T   >  0). We also describe the experimental knowhow of the ultrahigh-sensitivity UPS of organic systems, which are very fragile upon ultraviolet-light irradiation, and some updates on our previously published results.